DIGITALIZATION OF SMALL AND MEDIUM-SIZED ENTERPRISES IN BULGARIA - Yuleva-Chuchulayna, Radostina (Revista Inclusiones, 2021)
Changes in the global market lead to a wider expansion of competition between small and medium-sized enterprises based in different countries, including Bulgaria. This requires bulgarian SME’s to take new strategies allowing more competitive advantages andimproving the common market through the introduction of modern techniques such as digitization of the organization. In order to be more easily introduced and fining digitalization in small and medium-sized businesses, managers need to know the main characteristics and legal features of the organization, its objectives, motives and striving. The level of digitization of the enterprise determines the way employees work, technological and manufacturing processes, the speed of service of loyal customers and the deliveries of the offered goods or services. The main objective of this development is aimed at clarifying the nature and specificities of small and medium-sized enterprises, as well as analyzing the extent and impact of digitalization on the activities of small and medium-sized enterprises in Bulgaria. The main research methods used in the development are contingent analysis, method of analysis and synthesis, intuitive and systematic approach, questionnaire survey.